Sports injuries in deaf japanese national soccer players - Someya, Y.; Anzawa, Y.; Shiota, Y.; Nagao, M.; Takazawa, Y. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Studying sports injuries is crucial to their prevention and plays a role in the continuation and promotion of sports activities. However, few studies of sports injury have been conducted on sporting events for parasports athletes, especially deaf athletes. A clear understanding of the difference between sports injuries in deaf and hearing athletes is important for prevention of injuries in deaf athletes. This purpose of this study was to clarify the incidence and characteristics of sports injuries in deaf soccer players. METHODS: Twenty-six participants (27.3±4.9 years old) who attended the Japanese national training camp for deaf soccer players in 2022-2023`s season were included in the study. The number of injuries, incidence (injuries/1000 player-hours [PH]), severity (number of days that the injured player can`t play), and injury burden (injury incidence × mean severity) were investigated over the one-year period. In addition, injury location, re-injury incidence, mode of onset, and injury mechanism were classified according to the definitions recommended by the International Olympic Committee and the Fédération International de Football Association. RESULTS: A total of 59 injuries occurred during the study period, with an incidence, severity, and injury burden of 10.1/1000 PH, 5.0 days, and 50.5 days/1000 PH, respectively. With respect to location, 89.8% of the injuries occurred in the lower extremity, with the ankle having the highest incidence and injury burden (2.7 injuries/1000 PH and 15.2 days/1000 PH). The most common diagnosis was ankle sprain, 68.8% of which were re-injuries or aggravation. The mode of onset of ankle sprain was a 50:50 ratio of contact to non-contact injuries. CONCLUSION: The characteristics of sports injuries in deaf Japanese national soccer players were similar to those in hearing soccer players, with a high incidence in the lower extremity. Ankle sprain had the highest incidence in deaf soccer players. To clearly characterize sports injuries in deaf soccer players, effects of intrinsic factors, such as balance performance, should be evaluated in future studies.